Manajemen Sumber Daya Manusia Hijau (Green HRM): Sebuah Tinjauan Literature - Sariafriza; Muammar Khadafi (Management Studies and Business journal, 2024)
In the midst of the issue of increasing environmental damage due to the production process, green resource management is needed to minimize this condition. Green resource management is a company policy in managing human resources in a sustainable manner by involving environmental aspects to preserve nature in company management. This research includes qualitative descriptive research. Descriptive research is aimed at explaining the concept of Green Human Resources Management (GHRM). The findings of this research show that the implementation of Green Human Resources Management (GHRM) plays an important role in improving positive environmental outcomes'